EFFECT PLANTING DEPTH AND SOME PRE-TREATMENTS ON THE GERMINATION OF SEEDS AND SEEDING GROWTH OF CORIANDRUM SATIVUM L. - Gihan Y. Q. Saleh (Mesopotamia Journal of Agriculture)
In this research we've studied the effect of Some Pre-Treatments on the germination of Coriandrum Sativum L. seeds such as surface and planting at 2.5cm depth from soil surface as well as using the technology of pre-soaking with the following treatments : without soaking in water, soaking in Gibberellin with a concentration of 200ml.g/lit, soaking in water, soaking in ether petroleum, soaking in ethanol and soaking in concentrated sulfuric acid. Findings showed that the surface planting has improved seeds, germination and seedlings growth for all the features under study comparing with planting at a depth of 2.5cm. Findings of coefficient's overlap showed that surface planting and processing with Gibberellin with a concentration of 200ml.glit gave the best results. Seeds germinated early with an increased germination percentage which were 8.69 day and 75% respectively, as well as an increase in the fresh and dry weight of the root and green gross and an increase in the length of the longest seedling, then followed by soaking in water. Using the ether petroleum and ethanol showed no great significant effect on the features being studied; whereas the using of concentrated sulfuric acid showed a negative effect on germination for all features which were germination percentage 25.83 while which were concentrated 36.33%.